The mission of God : unlocking the Bible's grand narrative - Wright, Christopher J. H., 1947- (Downers Grove, Illinois, IVP Academic, 2006)
Most Christians would agree that the Bible provides a basis for mission. But Christopher Wright boldly maintains that mission is bigger than that--there is in fact a missional basis for the Bible! The entire Bible is generated by and is all about God's mission. In order to understand the Bible, we need a missional hermeneutic of the Bible, an interpretive perspective that is in tune with this great missional theme. We need to see the "big picture" of God's mission and how the familiar bits and pieces fit into the grand narrative of Scripture. Beginning with the Old Testament and the groundwork it lays for understanding who God is, what he has called his people to be and do, and how the nations fit into God's mission, Wright gives us a new hermeneutical perspective on Scripture. This new perspective provides a solid and expansive basis for holistic mission. Wright emphasizes throughout a holistic mission as the proper shape of Christian mission. God's mission is to reclaim the world--and that includes the created order--and God's people have a designated role to play in that mission.
The Bible and mission -- The God of mission -- The people of mission -- The arena of mission.
Includes bibliographical references (pages 537-558) and indexes.
Keywords: Missions -- Theory; God (Christianity) -- Will; Mission of the church